2011
DOI: 10.15288/jsad.2011.72.567
|View full text |Cite
|
Sign up to set email alerts
|

Drug and Alcohol Involvement in Four Types of Fatal Crashes

Abstract: Objective: The aim of this study was to explore the relationship of drunk and drugged driving to the occurrence of fatal crashes associated with speeding, failure to obey/yield, inattention, and seat belt nonuse. Method: We examined data for fatally injured drivers involved in single-vehicle crashes killed in states in which more than 79% of the drivers were tested for drugs other than alcohol and had a known result. Results: About 25% of the drivers tested positive for drugs, a fi gure almost double that esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 13 publications
6
41
0
Order By: Relevance
“…Downloaded by [University of Delaware] at 05:20 04 October 2014 Drugged driving motor vehicle collisions resulted in more injuries among males compared to females in the current study. These results are comparable to the results of national, state, and local studies and correlate with the U.S. male-to-female ratio for driver's licenses in persons younger than 45; among those over 45 years of age, females have a higher proportion of driver's licenses (CDC 2006;Romano and Voas 2011;Sivak and Schoettle 2012;Walsh et al 2005). These results may indicate more risk-taking behaviors among young males while driving, elevated drug use among males compared to females, or elevated concurrent alcohol and drug use, or polydrug abuse, among males compared to females that can profoundly affect judgment while driving, which results in more motor vehicle collisions.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Downloaded by [University of Delaware] at 05:20 04 October 2014 Drugged driving motor vehicle collisions resulted in more injuries among males compared to females in the current study. These results are comparable to the results of national, state, and local studies and correlate with the U.S. male-to-female ratio for driver's licenses in persons younger than 45; among those over 45 years of age, females have a higher proportion of driver's licenses (CDC 2006;Romano and Voas 2011;Sivak and Schoettle 2012;Walsh et al 2005). These results may indicate more risk-taking behaviors among young males while driving, elevated drug use among males compared to females, or elevated concurrent alcohol and drug use, or polydrug abuse, among males compared to females that can profoundly affect judgment while driving, which results in more motor vehicle collisions.…”
Section: Discussionsupporting
confidence: 76%
“…Among drivers admitted to a level-1 trauma center over a 90-day period, half of the drivers tested positive for drugs (Walsh et al 2005). In fatal singlevehicle crashes nationwide (excluding buses and farm equipment), one quarter of drivers who were fatally injured tested positive for drugs; marijuana and stimulants were involved in approximately 23 percent each of the drug-involved crashes (Romano and Voas 2011). In West Virginia alone, 7.9 percent of drivers who died in a motor vehicle collision tested positive for opioids and/or depressants (CDC 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The possibility that drivers of different racial/ethnic group membership show different patterns of drugged driving suggests the possibility of bias if those patterns are left unaccounted. Nevertheless, recent studies have shown the contribution of drugs other than alcohol to crash risk to be much smaller than that by alcohol (Bernhoft, 2011; Hargutt, Krüger, & Knoche, 2011; Hels et al, 2011; Romano & Pollini, 2013; Romano & Voas, 2011; Romano, Voas , Torres-Saavedra, & Lacey, 2013, in press), therefore reducing the potential bias that failing to account for drugs other than alcohol may have on alcohol-related risk estimates. Finally, our study implicitly assumes that all drivers follow similar time-based patterns of drinking as well as of drinking and driving, regardless of their racial and ethnic membership.…”
Section: Discussionmentioning
confidence: 99%
“…About one third of fatally injured drivers in the United States tested positive for nonalcohol drugs and 20% tested positive for two or more drugs (Brady & Li 2013; Romano & Voas 2011; Kaplan et al 2006). The prevalence of non-alcohol drugs in weekend nighttime drivers is about 20% (Berning et al 2015).…”
Section: Introductionmentioning
confidence: 99%